Potential benefits and neural correlates of acupuncture treatment with or without physiotherapy on resting state functional connectivity in ischemic stroke patients with unilateral limb dysfunction - Fouch, Sone (Department of Human Biology, 2025)
Introduction: Stroke patients often have lasting physical and cognitive impairments, leading to functional dependence even after discharge from hospital. Acupuncture has been recommended by the World Health Organisation (WHO) as an adjunctive treatment for stroke. Physiotherapy serves as the primary rehabilitation approach in South Africa and numerous other Western nations. Despite their widespread use, the precise mechanisms underlying both acupuncture and physiotherapy remain elusive, and the neurological alterations following extended rehabilitation programs are yet to be defined. Resting-state functional magnetic resonance imaging (rs-fMRI) is a non-invasive technique used to map brain regions that are temporally correlated, indicative of functional connectivity, during periods of rest. In the present study, treatment-related alterations in brain RSFC in ischaemic stroke patients with unilateral limb dysfunction were randomised to receive either 1) True Acupuncture (TA), 2) TA and Physiotherapy (PT), or 3) PT and Sham Acupuncture (SA), representing a placebo or nonacupoint acupuncture. Methods: Right-handed participants were recruited from the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, including 23 stroke patients (58.5±8.0 yrs.) and 10 healthy controls (53.9±6.9 yrs.). As part of a stroke rehabilitation programme, stroke patients were assigned to one of the three treatment arms: TA alone (6 participants), TA with PT (7 participants), or SA with PT (10 participants). Each participants received 5 sessions over 3 weeks. Fugl-Meyer Assessment (FMA) data were collected before, after, and during (on day 8) treatment. MRI scans were performed on a 3T Skyra Scanner (Siemens, Erlangen, Germany) before and after the 3-week rehabilitation programme, including rs-fMRI using a gradient echo EPI sequence and T1-weighted structural images using an MPRAGE sequence. Healthy controls underwent a single scan without treatment. Rs-fMRI data were pre-processed using AFNI_proc.py. Eleven resting-state networks (RSNs) were identified through group independent component analysis (ICA) using FSL-MELODIC in data from the healthy controls. Dual regression and randomise in FSL were then applied to identify the clusters within the identified resting state networks (RSNs) showing significant differences (at p<0.01; cluster size threshold at α<0.05). The mean Z-score within each cluster was subsequently correlated to the FMA scores. Results: Before treatment, lower RSFC in 2 clusters in the precuneus within the Default Mode Network (DMN) and the Ventral Attention Network were found in the TA with PT group compared to the TA only and SA with PT groups. No significant differences in mean Z-scores within these two clusters were seen among the three groups after treatment. After treatment, differences in RSFC among groups were found in five regions within three networks, including the cingulate gyrus and the precuneus in the DMN, the orbitofrontal cortex in the executive control network, and the inferior and superolateral occipital lobe in the visual network. In all five of these regions, patients receiving TA+PT showed a significantly higher RSFC compared to individuals in the other groups. There were no significant differences in RSFC between groups in these five regions before treatment. After receiving TA+PT treatment, patients demonstrated higher resting-state functional connectivity (RSFC) compared to themselves before treatment in nine regions spanning four resting-state networks (RSNs), including the bilateral precuneus, right (R) anterior calcarine sulcus, R primary motor cortex, and left (L) angular gyrus in the first DMN; the bilateral precuneus in the second DMN; the R visual cortex, R posterior lingual gyrus and L visual cortex in the visual network; and the R posterior cingulate sulcus in the ventral attention network. However, after SA+PT treatment, individuals in the group exhibited lower RSFC compared to themselves before treatment in two regions within two networks, including the R postcentral gyrus in the somatosensory network and the L lingual gyrus in the visual network. All three treatment groups showed a significant increase in FMA scores from before treatment, to after treatment. No significant differences were found when comparing FMA scores between treatment groups. The TA+PT group's results showed a significant positive correlation between RSFC and FMA scores. Conclusions: Stroke patients who received one of three treatments demonstrated improved FMA scores, with no significant differences in FMA scores observed among the three treatment arms after treatment. Patients in the TA+PT group showed significant changes in key brain regions associated with cognition, sensorimotor integration, and motor function. Specifically, increases in RSFC within the precuneus, motor cortex, and posterior cingulate sulcus, which are involved in neural recovery and cognitive improvement. In contrast, the SA+PT group exhibited RSFC decreases within somatosensory and visual networks, indicating a different pattern of neural recognition. After treatment, patients in the TA+PT group exhibited higher RSFC in the precuneus in the DMN and executive control network. These findings highlight the potential efficacy of combining TA with PT for stroke rehabilitation, suggesting that this approach may facilitate positive neural adaptations. However, the study also highlights the necessity for further investigation with larger sample sizes and extended treatment durations to comprehensively grasp the efficacy and underlying mechanisms of this integrated approach